ANALYSIS OF THE IMPLEMENTATION OF THE KALEKE VILLAGE HEAD REGULATION NO. 1 OF 2024 FROM THE PERSPECTIVE OF FIQH ECOLOGY - Moh Helmi; Sitti Aisya; Wahyuni (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2026)
This study aims to analyze the implementation of the Kaleke Village Head Regulation (Perkades) No. 1 of 2024 concerning the Spring Water Maintenance and Management System and to examine it from the perspective of Fiqh Ecology. The research employed an empirical juridical method using sociological jurisprudence and statute approach. Data were collected through interviews, observations, and documentation and analyzed qualitatively using descriptive analysis. The findings indicate that the Perkades has been implemented through collaboration among the Village Government, the Village-Owned Enterprise (BUMDes), and the Tourism Awareness Group (Pokdarwis) in Spring Water conservation, water-use monitoring, public education, and conservation fee management. The implementation has been supported by community participation and religious values; however, challenges remain, including unauthorized water extraction using water pumps (alkon), domestic activities around the spring area, suboptimal public compliance, and the need for greater transparency in conservation fund management. From the perspective of Fiqh Ecology, the implementation of the Perkades reflects the principles of tauhid, khalifah, amanah and mas'uliyyah, justice (al-'adl), and the prohibition of environmental destruction (nahy 'an al-fasād). The conservation fee of IDR 1,000 per gallon serves as a conservation financing mechanism rather than a form of commercialization of water.